Hydrocarbon Cycling in the Tokamachi Mud Volcano (Japan): Insights from Isotopologue and Metataxonomic Analyses - Alexis Gilbert; Mayuko Nakagawa; Koudai Taguchi; Naizhong Zhang; Akifumi Nishida; Naohiro Yoshida (Microorganisms, 2022)
Understanding hydrocarbon cycling in the subsurface is important in various disciplines including climate science, energy resources and astrobiology. Mud volcanoes provide insights into biogeochemical processes occurring in the subsurface. They are usually associated with natural gas reservoirs consisting mainly of methane and other hydrocarbons as well as CO2. Stable isotopes have been used to decipher the sources and sinks of hydrocarbons in the subsurface, although the interpretation can be ambiguous due to the numerous processes involved. Here we report new data for hydrocarbon isotope analysis, including position-specific isotope composition of propane, for samples from the Tokamachi mud volcano area, Japan. The data suggest that C2+ hydrocarbons are being biodegraded, with indirect production of methane (“secondary methanogenesis”). Data from chemical and isotopic composition are discussed with regard to 16S rRNA analysis, which exhibits the presence of hydrogenotrophic and acetoclastic methoanogens. Overall, the combination of isotopologue analysis with 16S rRNA gene data allows refining of our understanding of hydrocarbon cycling in subsurface environments.